2019
DOI: 10.24198/pjd.vol31no2.22863
|View full text |Cite
|
Sign up to set email alerts
|

Differences of young adult smokers and non-smokers saliva reviewed by salivary pH, viscosity, and volume

Abstract: Introduction: Salivary pH, viscosity and volume play an important role in maintaining tooth and oral tissue integrity. The purpose of this research was to evaluate the difference of young adult smokers and non-smokers saliva reviewed by its pH, viscosity and volume. Methods: The research sample of 28 smokers and 24 non-smokers. Saliva was collected by spitting method then the pH, viscosity and volume was measured. The data was analyze using independent sample t-test and chi-square. Results: The result indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
1
5
0
Order By: Relevance
“…33,34 Interestingly, smoking has been proven to reduce SFR. Confirming the previous observations, [35][36][37][38][39][40][41][42][43] Singh et al demonstrated a significant decrease in SFR in cigarette smokers. 38 One of the mechanisms leading to a reduced SFR may be alterations in the tissue architecture of the salivary glands.…”
Section: Effect Of Cigarette Smoking On the Flow Rate Viscosity And B...supporting
confidence: 82%
See 3 more Smart Citations
“…33,34 Interestingly, smoking has been proven to reduce SFR. Confirming the previous observations, [35][36][37][38][39][40][41][42][43] Singh et al demonstrated a significant decrease in SFR in cigarette smokers. 38 One of the mechanisms leading to a reduced SFR may be alterations in the tissue architecture of the salivary glands.…”
Section: Effect Of Cigarette Smoking On the Flow Rate Viscosity And B...supporting
confidence: 82%
“…36 In the group of non-smokers, 75% of participants had normal saliva viscosity, and 25% had moderate saliva viscosity, indicating that no subjects had poor saliva viscosity. 36 An increase in saliva viscosity due to smoking may be connected with a high sensitivity of the parotid glands to tobacco smoke toxins. 57,58 The parotid glands are responsible for producing watery, serous saliva, and its absence is compensated by the submandibular and sublingual salivary glands, which secrete thicker saliva with a high mucin content.…”
Section: Effect Of Cigarette Smoking On the Flow Rate Viscosity And B...mentioning
confidence: 91%
See 2 more Smart Citations
“…In this sense, tobacco can also alter the volume, viscosity, and pH of saliva. This was revealed in a comparative study between smokers and non-smokers, finding that the salivary volume and pH of smokers was lower in non-smokers and the salivary viscosity of smokers was greater in non-smokers [47].…”
Section: Sample-related Challengesmentioning
confidence: 90%